Pelaksanaan Asimilasi Narapidana dalam Rangka Pencegahan dan Penanggulangan Penyebaran Covid-19 di Wilayah Hukum Lembaga Pemasyarakatan Kelas IIA Padang - Ikhwan, Indah; Danil, Elwi; Sabri, Fadillah (Universitas Ekasakti, 2023)
The government implemented the policy to prevent the Covid-19 virus in correctional institutions by issuing Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 32 of 2020 concerning Requirements for Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Preventing and Controlling the Spread of Covid-19 which was later changed to Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 43 of 2021 concerning the Second Amendment to the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 32 of 2020 concerning Conditions for Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Preventing and Controlling the Spread of Covid-19 . The existence of this policy of providing home assimilation has become a social controversy in society because of the repetition of criminal acts committed by prisoners while undergoing the home assimilation program. The research method used is empirical juridical. This research utilizes primary data and secondary data. The results of the research show that the implementation of home assimilation is in accordance with the applicable SOP, although there are still those who repeat criminal acts which cause their home assimilation to be revoked. Implementing home assimilation is one way to reduce overcapacity in correctional institutions. Supervision of the implementation of home assimilation is carried out by visiting clients' homes, via telephone and video calls. In implementing home assimilation, the obstacles faced are influenced by five factors in law enforcement.